Measuring organization capital - Atkeson, Andrew 1961-; Kehoe, Patrick J. (NBER working paper series, 2002)
In the manufacturing sector of the U.S. economy, nearly 9% of output is not accounted for as payments to either physical capital or labor. The value of this output is a little larger than the value of the stock of physical capital. We build a model to measure how much of this output can be attributed to payments to organization capital-organization-specific knowledge that is built up with experience. We find that roughly 4% of output can be accounted for as payments to organization capital and that this capital has roughly two-thirds the value of the stock of physical capital.